Planar Hall effect from the surface of topological insulators. Issue 1 (December 2017) - Taskin, A.; Legg, Henry; Yang, Fan; Sasaki, Satoshi; Kanai, Yasushi; Matsumoto, Kazuhiko; Rosch, Achim; Ando, Yoichi
Abstract A prominent feature of topological insulators (TIs) is the surface states comprising of spin-nondegenerate massless Dirac fermions. Recent technical advances have made it possible to address the surface transport properties of TI thin films by tuning the Fermi levels of both top and bottom surfaces. Here we report our discovery of a novel planar Hall effect (PHE) from the TI surface, which results from a hitherto-unknown resistivity anisotropy induced by an in-plane magnetic field. This effect is observed in dual-gated devices of bulk-insulating Bi2−x Sbx Te3 thin films, where the field-induced anisotropy presents a strong dependence on the gate voltage with a characteristic two-peak structure near the Dirac point. The origin of PHE is the peculiar time-reversal-breaking effect of an in-plane magnetic field, which anisotropically lifts the protection of surface Dirac fermions from backscattering. The observed PHE provides a useful tool to analyze and manipulate the topological protection of the TI surface. Topological surface states can lose their protection in many ways but the subtle mechanisms remain far from well understood. Here, Taskin et al. report a novel planar Hall effect in dual-gated Bi2−x Sbx Te3 thin films, originating from anisotropic lifting of time reversal symmetry protection by an in-plane magnetic field.